Adoption Pattern of Farm-Machinery based Solutions for In-situ Paddy Straw Management in Punjab (Indian Journal of Extension Education, 2023)
Farmers burn paddy residues in the field harvested by combine harvester to prepare fields for sowing of the next crop in the narrow window between paddy harvesting and the next sowing. Punjab Agricultural University has carried out extensive research on farm machinery for in-situ paddy straw management and promoted technologies in Punjab from 2018 to 2022 under the “Promotion of Agricultural Mechanization for in-situ Management of Crop Residue” scheme. A survey was carried out to assess the adoption pattern of these technologies by Punjab farmers. The adoption of Happy seeder was maximum (16.80%) among different technologies during 2019 while Super seeder was preferred and accepted on a large scale (14.99%) during 2020. Farmers growing potatoes and other winter crops preferred residue incorporation using chopper, rotavator, MB plough, or harrow and adoption varied from 9.17 per cent to 20.4 per cent over five years. Overall, paddy straw management has increased from 20.49 per cent during 2016 to 49.91 per cent during 2023.